Reconfiguring dualism and difference: the (il)logic of theory/academic knowledge and development/practice in higher education research and practice - Walker, Melanie (South African Journal of Higher Education, 2016)
This paper considers the dualism of theory or academic knowledge and development or practice. This dualism is fairly well embedded in universities and may not be helpful for both knowledge making or practices, such as teaching. The paper revisits the dualism in order to construct an ethics of higher education which draws substantially on both theory and practice in order to address Michael Sandel’s question: What is the right thing to do. Power and boundaries underpin the dualism; these are considered and an argument made for productive alignments rather than dissolving one set of practices into another. Three issues of concern to the author frame the argument: the work that theory does but equally the work that practice does; dialogic knowledge transfers; and which theories get taken up in higher education with what practical effects. Some implications for change are then outlined.